La asignación y uso de recursos económicos para protección ambiental y su relación con el nivel de gasto público en el Gobierno Regional de Ucayali durante el periodo 2010–2023 - Figueroa Rojas, Niels Cein (2025)
This research analyzes the relationship between the allocation and use of economic resources for environmental protection and the level of public spending in the Regional Government of Ucayali during the period 2010-2023. Through a quantitative and correlational design approach, we evaluate how investment in environmental protection influences the efficiency of government management and tax collection. The results show a significant positive evaluation between the allocation of environmental resources and the level of public spending (Rho = 0.7524, p < 0.05), as well as a moderate relationship between the execution of these resources and the general efficiency of the regional government (Rho = 0.5388, p < 0.05). Furthermore, a positive trade off was found between the allocation of resources for environmental protection and tax collection (Rho = 0.5822, p < 0.05), suggesting that greater investment in environmental sustainability can improve the tax base. These findings underscore the importance of public policies that prioritize investment in environmental protection to improve both the ecological sustainability and economic development of the region. The research concludes that efficient and adequate management of resources intended for environmental protection is essential to promote sustainable regional development in Ucayali, benefiting both the environment and the local population.